Gambaran Self Compassion : Bagaimana Mahasiswa Menerima Dirinya Ketika Berada dalam Keadaan yang Terpuruk? - Febriyani, Devi; Hastuti, Evi Srinur; Khairina, Nida (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2021)
Students are learners who are in the career exploration stage. In this stage, they begin looking for career that suitable to choose in order to prepare their future. Many challenges at this stage often make students meet failure and downturn. If students can assess the failure, self-deficiency, and being down are normal things that happen to humans, then students will be able to handle the negative emotions they feel and not judge themselves. In the concept of Psychology, this is known as self-compassion, which is a state where individuals are able to accept and remain kind to themselves, especially when faced a failure. Self-compassion is one of the aspects that students need to have when handling a failure, especially for preparing their career choices. However, not all students have self-compassion. There are some students in the 2017 batch of the UNIBI Management Study Program who actually labeling themselves with something negative and don’t accept their failure in the studies. This study aims to find out about the self-compassion in 2017 batch students of the UNIBI Management Study Programme. Using quantitative research methods, this study was conducted on 69 students using the Self-Compassion Scale measuring instrument. Based on descriptive tests and analyses, the results show that 22 students (32%) are compassionate, which is able to accept themselves when they experience failure. And 47 students (68%) are uncompassionate, or less able to accept themselves when faced with failure.